2019
DOI: 10.1111/jgs.16257
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reproductive History With Motor Function and Disability in Aging Women

Abstract: BACKGROUND/OBJECTIVES The associations of reproductive history and motor function are controversial. DESIGN Prospective cohort study with 10 years of follow‐up. SETTING Three French cities between 1999 and 2011. PARTICIPANTS A total of 3043 community‐dwelling women from the Three‐City Dijon study population. MEASUREMENTS We examined the cross‐sectional and longitudinal association of age at menopause, artificial menopause, and parity with walking speed (WS) using linear regression and linear mixed models, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Two studies reported that women who underwent PBO, mainly before the age of 45 years, self-reported more physical function limitations, had greater declines in gait speed, and an increased risk of disability. 39,40 However, self-reported PBO was not associated with a greater risk of prefrailty or frailty over 18 years of follow-up in the Study of Osteoporotic Fractures. 41 Our results are more consistent with the first two studies because women who underwent PBO with or without hysterectomy before the age of 46 years walked shorter distances in the 6-minute walk test.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies reported that women who underwent PBO, mainly before the age of 45 years, self-reported more physical function limitations, had greater declines in gait speed, and an increased risk of disability. 39,40 However, self-reported PBO was not associated with a greater risk of prefrailty or frailty over 18 years of follow-up in the Study of Osteoporotic Fractures. 41 Our results are more consistent with the first two studies because women who underwent PBO with or without hysterectomy before the age of 46 years walked shorter distances in the 6-minute walk test.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies examining the relationship between PBO and physical function yielded conflicting results. Two studies reported that women who underwent PBO, mainly before the age of 45 years, self-reported more physical function limitations, had greater declines in gait speed, and an increased risk of disability 39,40 . However, self-reported PBO was not associated with a greater risk of prefrailty or frailty over 18 years of follow-up in the Study of Osteoporotic Fractures 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Research reports have shown that women aged 65 or older who have given birth to four or more children have a higher risk of disability compared to women with three or fewer children [31,32]. Another study in the United States found that postmenopausal women with three or more children had poorer physical functioning than women who had not given birth [33]. A study based on the Korean population showed that higher parity is independently associated with an increased risk of metabolic syndrome in postmenopausal women [34].…”
Section: Resultsmentioning
confidence: 99%
“…Participants who have a high number of children might be under more stress and pressure, which may put them at risk of more severe symptoms [ 20 ]. It has been reported women with three or more children were at higher risk of disability in advanced age compared to nulliparous women [ 9 ]. Nulliparity is also associated with an early onset of menopause as parous women have an anovulatory period that delays menopause [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive history has been found as an involved factor in menopausal symptoms. It has been demonstrated that early age at menopause and higher parity have a deleterious effect on the motor function that persists in older people [ 9 ]. It has been reported in a systematic review and meta-analysis that previous use of oral contraceptives, age at menarche ≥ 13, and having at least one live birth are associated with later menopause.…”
Section: Introductionmentioning
confidence: 99%